Results of a fall prevention educational intervention for residential construction. (November 2016) - Evanoff, Bradley; Dale, Ann Marie; Zeringue, Angelique; Fuchs, Mark; Gaal, John; Lipscomb, Hester J.; Kaskutas, Vicki
Highlights: Falls from heights abound in residential construction and research is limited. Hands-on training improved apprentice carpenters' knowledge, behaviors, and falls. Program can be adapted to other apprenticeships and new worker training programs. Abstract: Falls from height remain the leading cause of fatalities in residential construction. We used results from a comprehensive needs assessment to guide changes in fall prevention training in a joint union-contractor carpenter apprenticeship program; including surveys of 1018 apprentice carpenter and observational audits at 197 residential construction sites. The revised training utilized hands-on, participatory training methods preferred by the learners to address the safety gaps in the curriculum; including ladder use, leading edge work, truss setting, and use of scaffolding and personal fall arrest. We compared apprentice surveys (n = 1273) and residential worksite audits (n = 207) 1–2 years post-training with baseline measures. Apprentices working residential construction were more likely to fall from heights (OR = 2.26, 95% CI 1.59–3.21) than those working commercial construction. The revised training resulted in improved fall safety knowledge, self-reported worksite behaviors, risk perceptions, and safety climate, even after adjusting for temporal trends. We also observed significant improvements in fall safety compliance in most domains of the worksite audit, with larger changes observed in areas emphasized in the training, demonstrating specificity of the effect. Greater effects were noted in small and medium-sized contractors, who often have limited resources to devote to safety. Self-reported falls fell from 18.2 to 14.5 per 100 person-years of work. This research supports growing evidence that worksite safety can be improved by training. This curriculum could be readily adapted to other union apprenticeship programs. Fall safety of inexperienced residential construction workers' should remain a focus of future research.